Nanocompósitos de PHB e argilomineral montmorilonita contendo interfaces responsivas a estímulos externos - Meriane Cristine dos Santos (2013)
Nanocomposites with interfaces that can respond to external stimuli were developed based upon the incorporation of poly(ethylene glycol) (PEG) and montmorillonite clay mineral grafted with poly(N-isopropylacrylamide) (PNIPA) into a poly(hydroxybutyrate) (PHB) matrix. The surface of the clay was initially modified with a silane coupling agent containing a vinyl group, followed by the polymerization with NIPA. The modified clay was characterized by infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), x-rays diffraction (DRX) and contact angle. The behavior of the PNIPA functionalized clay when submitted to changes in temperature was verified by measuring the particle size: the modified clay in aqueous solutions had its size 89% reduced when the temperature was changed from 25ºC to 40ºC. After the preparation of the grafted clay with PNIPA, the modified particles were in-corporated into PHB to yield composites. The characterization of the composites was accomplished by FTIR, TGA, dynamic scanning calorimetry (DSC), optical microsco-py, scanning electron microscopy and dynamic mechanical analysis (DMA). Tensile tests were performed in two different temperatures: 25ºC and 40ºC. The presence of the grafted clay with PNIPA reduced the strength and increased the strain at break of PHB at 25ºC. The increase in strain at break was accentuated at 40ºC. The contact angle measurements of the composites showed an increase in the hydrophobic behavior at 40ºC. The obtained results indicated an overall increase in the thermal and mechanical properties of PHB with the incorporation of the modified clay. Moreover, it was demon-strated that the obtained nanocomposites containing PNIPA modified clay yielded mate-rials that have smart interfaces that are able to respond to external stimuli, such as slight changes in temperature.